Tanggungjawab Terhadap Kurikulum Merdeka Belajar di Madrasah - Nurhamidin, Candra Puspitas; Yahiji, Kasim (Turabian: Jurnal Pendidikan Islam, 2024)
This research aims to examine the responsibility for implementing the independent learning curriculum in educational units in madrasah. This research is research that uses a qualitative approach with data collection techniques in this research using literature studies originating from books, articles and journals that discuss the independent learning curriculum theory. The results of this research show that the Independent Curriculum is an educational concept that provides teachers with greater freedom and autonomy in designing and implementing learning. The Merdeka Curriculum frees teachers from a curriculum that is too rigid and provides flexibility in determining teaching methods, lesson materials and assessments. Learning is carried out in accordance with the diversity of students, the development of talents and interests, and the needs of students. The role and responsibilities of the madrasa head is the main supporter in making policies within the smallest scope, namely the madrasa. Teachers play an important role in implementing the Independent Curriculum in achieving madrasah goals. Teachers are a key factor in implementing the curriculum and providing meaningful learning experiences for students, therefore, there is a need for continuous professional training and development so that teachers have a deep understanding of the curriculum, effective learning methods, and the ability to manage the classroom well.